Corporate governance factors influencing job satisfaction among banking sector employees in China - Lin, Yufei (2022)
This research intends to evaluate effective corporate governance elements impacting work satisfaction among employees in Chinese state-owned commercial banks. The research population comprised of all state-owned commercial banks (1.8 million employees) in China. Where the analysis and sampling unit contained all job titles. The research sample size was 271 employees, with 306 returned questionnaires, and 301 questionnaires evaluated after discarding the questionnaires that are not acceptable for analysis. The research demonstrated statistically significant effective corporate governance variables in dimensions of transparency, equality, and accountability to work satisfaction resulting in salaries and compensations, training and professional development, promotions to different degrees. The findings demonstrated a statistically significant influence of implementing effective corporate governance on job satisfaction among employees in Chinese state-owned commercial banks.